Pro: Liver Transplantation Should Be Considered in Select Patients With Acute Alcoholic Hepatitis. Issue 5 (31st May 2019) - Kubiliun, Maddie J.; Rich, Nicole E.; Singal, Amit; Mufti, Arjmand R.
Abstract : Watch a video presentation of this article